Vertical illusory self-motion through haptic stimulation of the feet - Nordahl, R.; Nilsson, N. C.; Turchet, L.; Serafin, S. (2012 IEEE VR Workshop on Perceptual Illusions in Virtual Environments, 2012)
Circular and linear self-motion illusions induced through visual and auditory stimuli have been studied rather extensively. While the ability of haptic stimuli to augment such illusions has been investigated, the self-motion illusions which primarily are induced by stimulation of the haptic modality remain relatively unexplored. In this paper, we present an experiment performed with the intention of investigating whether it is possible to use haptic stimulation of the main supporting areas of the feet to induce vertical illusory self-motion on behalf of unrestrained participants during exposure to a virtual environment depicting an elevator. The experiment was based on a within-subjects design where all participants were subjected to identical visual and auditory stimuli. The participants experienced a total of four conditions. For three of the conditions a different signal was used to generate the haptic feedback while the final condition included no haptic feedback. Analysis of self-reports were used to assess the participants' experience of illusory self-motion. The results indicate that such illusions are indeed possible. Significant differences were found between the condition including no haptic feedback and the remaining three conditions.